2021
DOI: 10.1038/s41541-021-00313-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SARS-CoV-2 D614G mutation on BNT162b2 vaccine-elicited neutralization

Abstract: Initial COVID-19 vaccine candidates were based on the original sequence of SARS-CoV-2. However, the virus has since accumulated mutations, among which the spike D614G is dominant in circulating virus, raising questions about potential virus escape from vaccine-elicited immunity. Here, we report that the D614G mutation modestly reduced (1.7–2.4-fold) SARS-CoV-2 neutralization by BNT162b2 vaccine-elicited mouse, rhesus, and human sera, concurring with the 95% vaccine efficacy observed in clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…Our studies of in vitro neutralization of a variety of SARS-CoV-2 variants have, to date, found that all tested BNT162b2-immune sera neutralize all tested variants. 13,[27][28][29][30][31] The variant with the greatest reduction in neutralization, B.1.351, which has been the dominant South African strain, is still neutralized at serum titers higher than those observed at the onset of protection against COVID-19 after the first vaccine dose. 9,13,19 Consistent with this finding, BNT162b2 had 100% (95% CI 53.5, 100.0) observed efficacy against COVID-19 in South Africa (placebo recipients, 9 cases; BNT162b2 recipients, 0 cases), and 8/9 cases for which sequence information could be obtained were B.1.351 lineage SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies of in vitro neutralization of a variety of SARS-CoV-2 variants have, to date, found that all tested BNT162b2-immune sera neutralize all tested variants. 13,[27][28][29][30][31] The variant with the greatest reduction in neutralization, B.1.351, which has been the dominant South African strain, is still neutralized at serum titers higher than those observed at the onset of protection against COVID-19 after the first vaccine dose. 9,13,19 Consistent with this finding, BNT162b2 had 100% (95% CI 53.5, 100.0) observed efficacy against COVID-19 in South Africa (placebo recipients, 9 cases; BNT162b2 recipients, 0 cases), and 8/9 cases for which sequence information could be obtained were B.1.351 lineage SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…D614G may also be responsible for increasing the number of spike proteins per virion 141,142 and the rate of S1/S2 cleavage 143 . Viruses with D614G have been slightly more susceptible to neutralization by mAbs, convalescent plasma and plasma from vaccinated individuals in some studies 138,144 and slightly more resistant to neutralization in other studies 136,145 .…”
Section: D614gmentioning
confidence: 99%
“…2). Except lineage A, all isolates (lineages B, P, and R) have the S gene D614G mutation located in the receptor-binding motif, which has been reported to have a modest impact on vaccine-elicited neutralization 21 . For each isolate we highlight key S protein amino acid differences in the antigenic regions of the amino-terminal domain (NTD), RBD-ACE2 interface, and furin cleavage site (FCS) (Figure 3a).…”
Section: Vaccine-induced Nab Against Variantsmentioning
confidence: 99%